Censure, éthique et propagande au sein de la revue URSS en construction - Jessica Watson (Les Cahiers de l'École du Louvre)
The photographic magazine URSS en construction was produced from 1929 to 1949 for propaganda purposes with the aim of showing Western countries the industrial and ideological power of the USSR. Certain eminent artists such as El Lissitzky and Aleksandr Rodchenko were contributors and, through their photomontages conveyed a utopian image of Stalinist society of the 1930s. Censorship or propaganda? How to understand their works today and how to locate the place of the artist in a totalitarian regime. The magazine URSS en construction sheds light on the ideological complexities at the heart of Soviet art and explores the dilemma between artistic integrity and survival.